Pengembangan E-LKPD Interaktif Menggunakan Live Worksheet untuk Meningkatkan Hasil Belajar Kognitif - Siska safitri; Muliani; Nuraini Fatmi; Safriana; Halimatus sakdiah (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Agama Islam Jamiatut Tarbiyah Lhoksukon, 2025)
This study aims to develop an interactive electronic student worksheet (E-LKPD) utilizing the Live Worksheet platform to enhance students' cognitive learning outcomes on the topic of static fluids. The development process followed the ADDIE model, which includes five stages: Analysis, Design, Development, Implementation, and Evaluation. The E-LKPD was validated by experts in media, content, and language, and was tested on 24 students from Class XI at MAN 3 Aceh Utara. Data were gathered through expert validation sheets, student response questionnaires, and pretest-posttest assessments. The findings showed that the E-LKPD was highly valid in terms of content accuracy, media presentation, and language clarity. Students responded enthusiastically to the learning tool, and its use led to a significant improvement in cognitive learning outcomes, as evidenced by the N-gain score. These results suggest that the interactive E-LKPD developed with Live Worksheet is both feasible and effective as a learning medium for static fluid concepts